Implementasi Metode Qiro’ah Dalam Pembelajaran Bahasa Arab di MI Al-Ikhlas Assunniyyah Kencong Jember - Furoidah, Asni; Zuhriyah, Hamidatus (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Learning Arabic is not easy. So we must be able to choose ways or methods to use in the learning process that can increase students’ interest and ability in maharag Qiro’ah. Here I only use the Qiro’ah method wuth the aim that students can read well and correctly. The implementation of the Qiro’ah method Arabic language learning is carried out it several stages, including preparation stage the teacher first introduces hijaiyyah letters and Arabic numbers meanwhile, the implementation stage consists of initial activities with a classical or private system. And in the evaluation stage, teachers carry out daily or weekly evaluations which aim to find out the extent of their abilities in learning maharah Qiro’ah.